Identifikasi Gaya Berpikir Matematis Mahasiswa melalui Penyelesaian Permasalahan Higher-Order Thinking - Siti Khoiruli Ummah; Tri Rahayu Handayani (Jurnal Elemen, 2019)
This research aimed to identify students' mathematical thinking style in mathematics education to resolve the higher-order thinking problem. The type of study was descriptive using qualitative data based on the vector analysis test. The vector analysis was identified by mathematical thinking style that divided into visual, analytic, and integration. This thinking style formed the qualitative data in the form of a description of the suitability of the student answer using indicators of any mathematical thinking styles. The subject whom students in the course of Vector Analysis Fourth Semester was interviewed after got mathematical thinking style data. The results showed that a lot of students has mathematical integration, that is, both visually and analytic. Students who have mathematical thinking style visually answered the question using a sketch of parallel vectors, perpendicular vectors, vector tangent, but they do not put the vector notation. Students who have analytical thinking styles differentiated vectors relationship using the verbal description of the appropriate definition that has been studied when they were in high school level. Students who have integrated mathematical thinking styles draw vectors using vector notation and explain verbally.